Italian Hermeticism and Romanian Oneirism: An Ideological Approach - Pavel, Ecaterina (Revista Transilvania, 2015)
The aim of this article is to draw a parallel between two totalitarian ideologies – fascist and communist – which reflect in the lives and works of two poets: Giuseppe Ungaretti and Daniel Turcea. The better to explore these issues, I want to set out two distinct objectives. The first is to describe, by comparing and contrasting, the two ideologies, in order to set the scene for a discussion on Italy’s fascist and Romania’s communist cultural policies, mainly in relation to literary culture. The second is to establish a connection between the two cultural policies and the lives of the discussed poets. By way of conclusion I will focus upon the influences and effects of the two ideologies in Ungaretti’s and Turcea’s literary works.
Keywords: Fascism; Communism; Hermeticism; Oneirism; Giuseppe Ungaretti; Daniel Turcea